Isaiah: Interpreted by Early Christian and Mediaeval Commentators. Translated and edited by Robert Louis Wilken - Sawyer, John F. A. (The journal of theological studies, 2008)
The Isaiah volume in the Church's Bible series is to be particularly welcomed for two reasons: first, because no other Old Testament prophet has had such an influence on the history of Christianity from New Testament times down to the present, worldwide, and second because it is by Robert Wilken, one of today's most learned and respected patristics authorities. The task was a herculean one, not only because the Book of Isaiah itself is one of the longest in the Bible, but also because, in addition to complete commentaries on Isaiah by Eusebius, Jerome, John Chrysostom, Cyril of Alexandria, Theodoret, and Thomas Aquinas, virtually all the other Christian writers of the period frequently quote and discuss Isaiah in their homilies, sermons, and commentaries on other books.